Aligned collagen scaffold combination with human spinal cord-derived neural stem cells to improve spinal cord injury repair. (24th August 2020) - Zou, Yunlong; Ma, Dezun; Shen, He; Zhao, Yannan; Xu, Bai; Fan, Yongheng; Sun, Zheng; Chen, Bing; Xue, Weiwei; Shi, Ya; Xiao, Zhifeng; Gu, Rui; et al.
Abstract : Neural stem/progenitor cell (NSPC)-based spinal cord injury (SCI) therapy is expected to bridge the lesion site by transplanting exogenous NSPCs for replacement of lost cells. Abstract : Neural stem/progenitor cell (NSPC)-based spinal cord injury (SCI) therapy is expected to bridge the lesion site by transplanting exogenous NSPCs for replacement of lost cells. The transplanted NSPCs produce a microenvironment conducive to neuronal regeneration, and ultimately, functional recovery. Although both human fetal brain- and spinal cord- derived NSPCs (hbNSPCs and hscNSPCs, respectively) have been used for SCI repair, it remains unclear whether hscNSPCs are a more appropriate stem cell source for transplantation than hbNSPCs. Therefore, in this study, we transplanted hbNSPCs or hscNSPCs into rats with complete transection SCI to monitor their differences in SCI treatment. An aligned collagen sponge scaffold (ACSS) was used here for cell retention. Aligned biomaterial scaffolds provide a support platform and favorable morphology for cell growth and differentiation, and guide axial axonal extension. The ACSS fabricated by our group has been previously reported to improve spinal cord repair by promoting neuronal regeneration and remyelination. Compared with the hbNSPC–ACSS, the hscNSPC–ACSS effectively promoted long-term cell survival and neuronal differentiation and improved the SCI microenvironment by reducing inflammation and glial scar formation. Furthermore, the transplanted hscNSPC–ACSS improved recovery of locomotor functions. Therefore, hscNSPCs appear to be a superior cell source to hbNSPCs for SCI cell therapy with greater potential clinical applications.